Археологічна культура і ландшафт - Ричков, М.О. (Археологія, 1995)
У статті йдеться про співвідношення в межах України ареалів 77 археологічних культур з природно-територіальними комплексами. Статья посвящена соотнесению ареалов археологических культур Украины с типами и видами ландшафта. Рассматриваются ареалы 77 археологических культур и типов памятников, начиная с мезолита и до средневековья. Столь большой временной диапазон культур позволил наметить ряд тенденций. Одна из них заключается в совпадении границ между синхронными культурами с границами между видами ландщафтов (89% случаев!). Такое совпадение представляется закономерным и может служить подтверждением известного тезиса о прямой связи территории определенного этноса с конкретным ландшафтом.
В то же время, наличие археологических культур с весьма широкими ареалами, включающими территорию нескольких типов ландшафта, может свидетельствовать о полиэтничности носителей этих культур. Однако, в каждом конкретном случае вопрос этничесокй интерпретации археологической культуры должен рассматриваться отдельно.
Соотнесение ареалов археологических культур с ландшафтами автор считает необходимой процедурой, предшествующей реконструкции исторической и этнической ситуации, основанной на анализе археологических материалов. The paper is devoted to comparison of areas of distribution of archaeological cultures of Ukraine with types and kinds of landscapes. Areas of distribution are considered for 77 archaeological cultures and types of relics beginning from mesolith till the Middle Ages. Such great time interval between the cultures permitted some tendencies to be outlined. One of them is the coincidence of the borders between synchronous cultures with the borders between types of landscapes (89% of cases). This coincidence seems to be natural and may serve confirmation of the known thesis on the direct relation between the territory of a definite ethnos and concrete landscape. At the same time archaeological cultures with rather wide areas of distribution which embrace the territory of several types of the landscape may prove the polyethnic character of carriers of these cultures. But the problem on ethnic interpretation of archaeological culture is to be treated specifically in each particular case.
The author thinks it to be a necessary procedure, to correlate archaeological cultures with landscapes. It must previous reconstruction of the historical and ethnic situation based on the analysis of archaeological and ethnic situation based on the analysis of archaeological findings.